CDK targeting of NBS1 promotes DNA-end resection, replication restart and homologous recombination - Falck, Jacob (Nature Publishing Group, 2012)
The conserved MRE11–RAD50–NBS1 (MRN) complex is an important sensor of DNA double-strand breaks (DSBs) and facilitates DNA repair by homologous recombination (HR) and end joining. Here, we identify NBS1 as a target of cyclin-dependent kinase (CDK) phosphorylation. We show that NBS1 serine 432 phosphorylation occurs in the S, G2 and M phases of the cell cycle and requires CDK activity. This modification stimulates MRN-dependent conversion of DSBs into structures that are substrates for repair by HR. Impairment of NBS1 phosphorylation not only negatively affects DSB repair by HR, but also prevents resumption of DNA replication after replication-fork stalling. Thus, CDK-mediated NBS1 phosphorylation defines a molecular switch that controls the choice of repair mode for DSBs.